2020
DOI: 10.1007/s40273-020-00946-y
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Analysis of Trial-Based Economic Evaluations to the Next Level: The Importance of Accounting for Clustering

Abstract: Objectives The aim of this study was to assess the performance and impact of multilevel modelling (MLM) compared with ordinary least squares (OLS) regression in trial-based economic evaluations with clustered data. Methods Three thousand datasets with balanced and unbalanced clusters were simulated with correlation coefficients between costs and effects of − 0.5, 0, and 0.5, and intraclass correlation coefficients (ICCs) varying between 0.05 and 0.30. Each scenario was analyzed using both MLM and OLS. Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…It is recommended to perform sensitivity analyses, using other methods such as selection and/or pattern-mixture models [77]. Furthermore, the handling of clustered data or longitudinal data was not investigated in this study, whereas failure to account for clustering will underestimate statistical uncertainty, can lead to inaccurate point estimates, and may in turn lead to incorrect inferences [10,71,79]. It is also important to note that the statistical challenges identified in this study are only a selection of possible statistical issues that might arise when analyzing trial-based economic evaluations [51].…”
Section: Comparison To Other Studies and Implications For Further Research And Practicementioning
confidence: 99%
“…It is recommended to perform sensitivity analyses, using other methods such as selection and/or pattern-mixture models [77]. Furthermore, the handling of clustered data or longitudinal data was not investigated in this study, whereas failure to account for clustering will underestimate statistical uncertainty, can lead to inaccurate point estimates, and may in turn lead to incorrect inferences [10,71,79]. It is also important to note that the statistical challenges identified in this study are only a selection of possible statistical issues that might arise when analyzing trial-based economic evaluations [51].…”
Section: Comparison To Other Studies and Implications For Further Research And Practicementioning
confidence: 99%
“…More recently another simulation study has shown that failing to take into account the clustered structure of the data in trial based economic evaluations using for instance ordinary least squares regression rather than MLMs leads to a substantial underestimation of the amount of variation [89]. We would also like to highlight that authors have seldomly specified the term bivariate (mixed/multilevel) model to explicitly acknowledge the (potential) correlation between costs and effectiveness data.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the imputed datasets will be pooled using Rubin's rules [62]. LMM, with the same three-level structure as described above, will be performed to estimate cost and effect differences [76]. In order to account for the highly skewed nature of cost data, bias-corrected and accelerated bootstrapping with 5000 replications will be used to estimate 95% confidence intervals around the cost differences.…”
Section: Economic Evaluationmentioning
confidence: 99%